2019
DOI: 10.1039/c9cc00923j
|View full text |Cite
|
Sign up to set email alerts
|

A consecutive process for C–C and C–N bond formation with high enantio-and diastereo-control: direct reductive amination of chiral ketones using hydrogenation catalysts

Abstract: A Rh catalyst derived from tri-(2-furyl)phosphine enables the direct reductive amination of 1,3-substituted ketones to occur in high yield and diastereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…[7] Some drug candidates carrying 3-substituted cyclohexylamines are also shown in Figure 2, along with the diseases that they target, [8] but efficient stereoselective methods for these chiral amines are still lacking. [9] We foresaw several obstacles in developing such an asymmetric transformation as in Figure 1 c: 1) a weakly donating ligand must be used to activate the p-allylic complex for external nucleophilic attack, but it may be easily displaced by alkylamines in the reaction mixture. 2) Asymmetric amination on substituted p-cycloallylic complexes of Pd is nontrivial, and only a limited number of examples of this kind have been reported.…”
mentioning
confidence: 99%
“…[7] Some drug candidates carrying 3-substituted cyclohexylamines are also shown in Figure 2, along with the diseases that they target, [8] but efficient stereoselective methods for these chiral amines are still lacking. [9] We foresaw several obstacles in developing such an asymmetric transformation as in Figure 1 c: 1) a weakly donating ligand must be used to activate the p-allylic complex for external nucleophilic attack, but it may be easily displaced by alkylamines in the reaction mixture. 2) Asymmetric amination on substituted p-cycloallylic complexes of Pd is nontrivial, and only a limited number of examples of this kind have been reported.…”
mentioning
confidence: 99%
“…The results obtained reveal Rh/BOBPHOS catalysts to be especially promising from the point of view of reactivity, and we next studied some challenging couplings that did not proceed well using Rh/BINAP catalysts during our previous study . The synthesis of chiral piperidones is also a desirable, yet challenging conjugate addition.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study we also found the use of heteroarylboronic acids, in particular 2‐furylboronic acid were challenging substrates for conjugate addition reactions . This is because heteroarylboronic acids are prone to protodeborylation .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations